Entrepreneurial Intentions of Women: A literature review - Bhairab Chandra Patra; Usha Lenka (Studia i Materiały)
Entrepreneurial intentions research has been steadily growing and has recently gained more momentum in the twenty-first century. But the field of women entrepreneurial intentions is still in a very nascent stage and lots of research work needs to be done on the entrepreneurial intentions of women. This study attempts to review the literature on entrepreneurial intentions of women and provide necessary actions to be taken. The purpose of this study is to identify the main sub-areas on which women entrepreneurial intentions research is being conducted by the researchers. The Author uses citation analysis as a tool for identifying the fields attracting the maximum attention of researchers and content analysis to find out the gist of research in each sub-area. Cross referencing method was also used to find the papers in the field that proved most impactful and have made significant changes in the advancement of the field. Each paper was analyzed in terms of its objectives, findings, and future scope. The study presents an insight of the area from the review. It also highlights the major gaps identified from academic literature.